Breastfeeding and caring for children: a qualitative exploration of the experiences of mothers with physical impairments in Ghana - Acheampong, Angela Kwartemaa (BMC Pregnancy Childbirth, 2020)
BACKGROUND: Breastfeeding and caring for children demand time, energy and effort. Mothers with physical impairments in Ghana require special needs to be able to achieve optimal motherhood as society demands. Globally, literature on breastfeeding and caring for children among mothers with physical disabilities is limited. Similarly, there is dearth of literature on the experiences of mothers with physical impairments in Ghana. Therefore, this study sought to add to literature by exploring the experiences of mothers with physical impairments with regards to breastfeeding and how they care for their children. METHODS: Qualitative descriptive exploratory design was used. Twelve mothers with physical impairments who had been purposively sampled gave informed consent before data was collected through in-depth one-on-one interviews. Data was recorded, transcribed and analyzed inductively using the content analysis technique. RESULTS: Mothers with physical impairments perceived breastfeeding as difficult and expensive due to issues relating to disruption of sleep, dysfunctional limbs and the need for breastfeeding mothers to eat nutritionally balanced meals. Participants felt prejudged and discriminated at different points in their daily encounters. CONCLUSION: Mothers with physical impairments have challenges. Therefore, attitudinal change should be advocated in the Ghanaian society with respect to issues concerning people living with disabilities.